Ecofeminism in Chris Wedge's Epic - Agus Ferani Istiharoh (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2019)
The aims of this study are to analyze the symbols of ecofeminism and the reflection of ecofeminism in Chris Wedge’s Epic (2013). In the first problem statement, the researcher analyzes some symbols of ecofeminism and the second, the researcher explains the reflection of ecofeminism in animation movie, Epic (2013). The object and primary data of this study is the movie entitled Epic (2013). The researcher applies two main theories, they are Peirce’s semiotics and ecofeminism. This research is kind of descriptive qualitative research. It means that the researcher explains every finding and interprets it based on the theory used. In collecting data, the researcher did steps such as watching movie, selecting primary data, and collecting the secondary data. While in procedure of analysis, the researcher did some steps as like preparing, reading, coding, describing, presenting, and interpreting. As the result, the researcher found that femininity and nature are the symbol of ecofeminism which represented with the existence of woman, flower, forest and animal. The existence of fairies are the sign of human’s nature, by that, ecofeminism is reflected in Epic (2013).